1981
DOI: 10.1002/chin.198148212
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: COMPOUNDS WITH ANTIULCER AND ANTISECRETORY ACTIVITY. I. 3‐ARYL‐BENZIMIDAZOLIN‐2‐ONES AND ‐THIONES

Abstract: Cyclisierung der o‐Phenylendiamine (I) mit Na‐ethylat gibt die Benzimidazolinone (II), die zu den Derivaten (III) alkyliert werden; die analog (II) synthetisierten Benzimidazolinone (IV) werden mit MeI zu (V) methyliert.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
17
0

Year Published

1987
1987
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 0 publications
0
17
0
Order By: Relevance
“…Thus, in aqueous alkali compounds 3c-e were alkylated with dimethyl sulfate to form 1-alkyl(aryl)-3-methylimidazol-2-ones 4c-e. The regioselective alkylation of imidazolones is confirmed by a number of literature analogs [13][14][15] and also by 1 H NMR spectral data: the signals of the protons of the NMe group are found in the 3.03-3.23 ppm region. The thioamides 5c-f were formed by the reactions of compounds 3c-f with hydrogen sulfide.…”
mentioning
confidence: 58%
“…Thus, in aqueous alkali compounds 3c-e were alkylated with dimethyl sulfate to form 1-alkyl(aryl)-3-methylimidazol-2-ones 4c-e. The regioselective alkylation of imidazolones is confirmed by a number of literature analogs [13][14][15] and also by 1 H NMR spectral data: the signals of the protons of the NMe group are found in the 3.03-3.23 ppm region. The thioamides 5c-f were formed by the reactions of compounds 3c-f with hydrogen sulfide.…”
mentioning
confidence: 58%
“…5‐Bromo‐1‐methyl‐3‐phenyl‐1 H ‐benzo[ d ]imidazol‐2(3 H )‐one (2x): Purification of the crude product by flash chromatography on silica gel (petroleum ether/ethyl acetate, 5:1) afforded 2x (74 % isolated yield) as a light yellow solid, m.p. 175–176 °C; ref 23. m.p.…”
Section: Methodsmentioning
confidence: 99%
“…[10][11][12] Our successful final step to 1 however uses the urea analogue of a Buchwald-Hartwig-type palladium-catalysed aryl-N coupling. This reaction has recently been popularised by Beletskaya who has shown that palladium-dibenzylideneacetone complexes and Xantphos ligands will N-arylate a wide range of ureas with aryl bromides and iodides.…”
Section: Scheme 3 Reagents and Conditionsmentioning
confidence: 99%